Analisis Spatial Malaria di Ekosistem Perbukitan Menoreh: Studi Kasus Malaria Bulan Septmeber-Desember 2015 - Sri Rejeki, Dwi Sarwani; Murhandarwati, Elsa Herdiana; Kusnanto, Hari (Universitas Ahmad Dahlan, 2018)
Background: Malaria is still becoming a public health problem in Indonesia. Menoreh Hills shows as one of the areas with endemic malaria in Java Island which has not been able to achieve the elimination target by 2015. Menoreh Hills is a cross-border administrative area, Central Java Province and Yogyakarta Special Region Province which has its own authority in financial management and budget allocation for malaria control. Furthermore, spatial analysis is very beneficial in controlling malaria, presenting geographic distribution of the disease, testing whether malaria is randomly distributed, evaluating the statistical significance of the disease cluster and showing as an early detection of outbreaks. Method: It applied an observational study with cross sectional spatial analysis design to observe the spreading, grouping pattern and the correlation between house distance to mosquito breeding and population density. The samples collected were 138 malaria cases and 138 controls. It required measurement of the coordinates to the house with GPS, identified breeding spots for mosquitoes around the house and collected the date data of malaria diagnosed in District Health Services. The location of the study covered 3 sub-districts as Malaria endemic areas namely Kaligesing, Bagelen and Kokap Sub-districs. Analysis of the data was conducted through ArcGIS, SaTScan dan Geoda softwares. Results: The malaria spreading in September-December 2015 was dominated in Kaligesing Sub-district of Purworejo Regency. Malaria cases were more common in areas with low density of population. The buffering analysis discovered that malaria patients were living near to the mosquito breeding (river, springs, and puddle). It was identified that there was 1 primary cluster and 2 secondary clusters which covered 3 districts at research location. Conclusion: The results of spatial analysis present that there is an incident of local malaria transmission in Menoreh hills. It requires an integrated malaria control program in Menoreh hills.